The Effect of Country of Origin and Perceived Quality on Buying Interest (Study on Consumers of Honda Motorcycles in Majalengka Regency) - Dudung Abdullah; Endah Prihartini (Jurnal Mantik, 2022)
This study aims to determine how the effect of country of origin and perceived quality on consumer buying interest in Honda motorcycles in Majalengka Regency, either partially or simultaneously. The research method uses a survey method with a descriptive and verification approach. The total population in this study is the people in Majalengka Regency. The sample used in this study were 100 respondents, the test instrument used in this study was the validity test and the reliability test. Analysis of the data used in this study is the classical assumption test, multiple regression analysis, coefficient of determination, and hypothesis testing. For the partial test using the t test and for the simultaneous test using the F test. The results show that the country of origin has a positive and significant effect on buying interest. This means that the better the country of origin, the higher the buying interest in Honda motorcycle consumers. Perceived quality has a positive and significant effect on buying interest. This means that the better the perceived quality, the higher the buying interest in Honda motorcycle consumers. Country of origin and perceived quality have a positive and significant effect on buying interest. This means that the better the country of origin and perceived quality, the higher the buying interest in Honda motorcycle consumers.